Experts’ Views on the Potential of Luxury Niche Agricultural Products for Rural Economic Development in Mexico and Other Nations with Similar Needs: ADelphi Study - Luis A. Flores; M Craig Edwards; Michael A. Schnelle; Craig E. Watters; J. Shane Robinson; Jeff Sallee (Journal of International Agricultural and Extension Education, 2021)
Economic development isessential for nations to realize growth and prosperity.For rural contexts, producingluxurynicheagricultural products, such as cut flowers, may offer unique opportunities. Nevertheless, variables exist that should be considered before starting suchventures. We sought to identify the potential of smallholder farmers in rural Mexico, and other nations with similar economic development needs, to grow high-value crops for luxury markets. Knowledgeable experts servedas panelistsduring the study’s three rounds of data collection, including researchers, extension educators, or other relevant professionals from Mexico and the United States. The initialround included three questions regarding 1) plant products, 2) a SWOT analysis framework, and 3) what smallholder farmers neededto achieve competitive advantages. In rounds two and three,theitems retained from the preceding round were presented within a SWOT framework to be rated using a six-point, Likert-type agreement scale. The cutoff percentage for consensus of agreement was 75.00%. After three rounds, 113 items reached consensus, including five categories of plant products; nine Strengths, 21 Weaknesses, 15 Opportunities, and 13 Threats; and 50 items regarding producers’ competitive advantages. Although our analysis revealedopportunities for smallholder farmers to successfully growspecialty crops for luxury niche markets,producer training and support mechanisms are needed to overcome weaknesses and threats while capitalizing on their strengths
Keywords: human capital; poverty; rural livelihoods; smallholder farmers; specialty crops; SWOT analysis